Implementasi Model Pembelajaran Problem Based Learning Berbantuan Media Timeline Dalam Meningkatkan Motivasi Belajar Sejarah Siswa Kelas XI MIPA 5 SMAN 2 Banda Aceh - Arisandi, Wall Fitri; Fauziah, Fauziah; Nurasiah*, Nurasiah (Universitas Syiah Kuala, 2023)
This study aims to look at the application of problem-based learning media assisted by timeline media to the learning motivation of class XI MIPA 5 students at SMAN 2 Banda Aceh. This study uses a qualitative approach with a type of classroom action research which is used to improve and improve the quality of a learning of problem-based learning models assisted by timeline media in increasing student learning motivation. As for the subjects in this study were all students of class XI MIPA 5, totaling 28 people. Data collection techniques used are observation and questionnaires. Based on the results of the study, it was found that there was a change in student behavior from cycle 1 to cycle 2. This was evidenced by the percentage of student scores in cycle 1 of 73.5% with the presentation criterion